Asumsi Hakikat Manusia Dalam Ilmu Pendidikan - Tri Astuti (Lembaga Pengembangan Kinerja Dosen, 2025)
Concepts about human nature are so diverse. Understanding the assumptions of human nature in education does not only include physical and psychological issues, but culture and other elements. Or in other words, humans are very complex creatures who need various elements in educational science to achieve success. Understanding human nature is very important in determining educational theory. History has proven that several assumptions about human nature from different points of view will determine the direction of educational theory, such as in the formation of the curriculum. The curriculum is the basis for forming character and human intelligence. This research is a qualitative descriptive research. The method used in this research is literature study. Primary data sources are journals and books related to human nature and educational science. Research validation is by triangulation. The results of the research are 1) the existence of stereotypical assumptions about human nature in education and 2) various designs and synchronization models as a form of human formation through education.